Application of asymmetric semi-circular bend test for determining mixed mode I + II fracture toughness of compacted soil material. (1st March 2022) - Aliha, M.R.M.; Jafari Haghighatpour, Pegah; Tavana, Alireza
Highlights: Application of asymmetric SCB (ASCB) specimen for investigating mixed mode I/II fracture of compacted soil. Obtaining critical mode mixity corresponding to the lowest fracture resistance for the tested soil. Nearly the same values were obtained for pure modes I and II fracture toughness (KIc and KIIc). Ability of maximum tangential stress criterion was examined for prediction of soil fracture data. Abstract: Soil is a common material for constructing the sub-grade layer in multi-layer pavement systems, buried pipelines and embankment dams. Failure and fracture of this material may result in undesired deformation and bad effect on the long-term performance of such structures. So far a number of testing methods and data are available for tensile type fracture (or mode I fracture) of soil materials. However, soil materials can experience mixed mode tensile-shear deformations in real situations due to external applied loads. Hence, a suitable testing method called asymmetric semi-circular bend (ASCB) specimen was proposed and utilized in this paper for characterizing the mixed mode tensile-shear cracking behavior of compacted soil materials. Full mode mixities ranging from pure mode I to pure mode II were tested on a clay soil material using the ASCB specimen. Depending on the mode mixity, the soil fracture toughness value was varied between 0.025 and 0.035 MPa.m 0.5 . The lowest fracture toughness was obtained at mixed mode I/II with nearly the same contribution of tensile and shear deformations. In this loading situation the effective fracture toughness ( K eff ) was approximately 30% less than K Ic and K IIc (i.e. pure modes I and II fracture toughness values, respectively). The fracture toughness values under pure mode I and pure mode II were almost equal. The maximum tangential stress criterion was also able to predict well the experimental mixed mode I/II soil fracture toughness results.